Different Crude Extracts of Cinnamomum tamala with Antioxidant and Antibacterial Capabilities - Kalauni, Surya Kant; Maharjan, Rasna; Pathak, Ishwor; Khadayat, Karan; Niraula, Muna; Thapa, Prakash (Amrit Research Journal, 2021)
In this present study, crude extracts of young and mature leaves of Cinnamomum tamala were evaluated for their antioxidant and antibacterial capabilities. The cold percolation method was carried out with polar solvents methanol and ethanol. The antioxidant activities of all the extracts were assessed by DPPH assay and antibacterial properties were performed against Staphylococcus aureus, Escherichia coli, Salmonella typhi, and Klebsiella pneumoniae by agar well diffusion method. All extracts were able to scavenge free radicals in which strong antioxidant activity was found in methanolic extract of young leaves, and its IC50 value was estimated as (67.19±14.96 μg/mL) at a concentration range of 31.25-500 μg/mL while IC50 value of standard ascorbic acid was found to be 33.53±0.97 μg/mL at the concentration range of 10-50 μg/mL. The ethanolic extract of leaves (ZOI = 19 mm) showed strong antibacterial activity while standard neomycin showed (ZOI = 23 mm) against Escherichia coli at a concentration of 50 μg/mL. These results may provide scientific evidence of the traditional uses of C. tamala. Isolation and characterization of pure active compounds should be done in the future.